Efetividade da antissepsia bucal prévia com clorexidina na prevenção da contaminação da moldagem com alginato e sua influência na distorção do material - Cubas, Glória Beatriz de Azevedo (2012)
The aims of this randomised controlled trial were to evaluate the influence of a preprocedural 0.12% chlorhexidine mouthrinse on the microbial contamination of dental impressions, subsequently disinfected with sodium hypoclorite or water (control). The second objective was to evaluate if aqueous solution of 0.12% chlorhexidine mixed with irreversible hydrocolloid powder would decrease microbial contamination of dental impressions. Forty subjects underwent maxillary dental impressions with irreversible hydrocolloid and were randomly divided into two groups (n=20) according to the preprocedural mouthrinse (0.12% chlorhexidine or placebo).The dental impressions were then divided into two subgroups and disinfected with sodium hypochlorite or water (control). In the second part, 20 subjects underwent maxillary dental impressions with irreversible hydrocolloid and randomly assigned into two groups according to the mixed agent used (0.12% chlorhexidine or water). Saliva and alginate samples were assessed for microbiological counts of total micro-organisms, total streptococci and Candida species. Surface roughness of the impressions and dimensional stability of the casts were also evaluated. Chlorhexidine preprocedural mouthrinse significantly reduced (p<0.05) microbial contamination. Small but significant alterations were produced on dimensional stability and surface quality when sodium hypochlorite was used as disinfectant after the impression (p=0.005). The results also showed that the use of aqueous 0.12% chlorhexidine mixed with the powder of irreversible hydrocolloid decreased the percentage of total micro-organisms and total Streptococci counts (p<0.001), without producing alterations in surface quality and dimensional stability. It can be concluded that 0.12% chlorhexidine used as preprocedural mouthrinse, or mixed with irreversible hydrocolloid powder, are effective methods in reducing microbial contamination of alginate impressions, without causing damage to the physical and mechanical properties of the material